Tissue Engineering in Pediatric Bladder Reconstruction—The Road to Success - Horst, Maya; Eberli, Daniel; Gobet, Rita; Salemi, Souzan (Frontiers in Pediatrics, 2019)
Several congenital disorders can cause endstage bladder disease and possibly renal damage in children. The current gold standard therapy is enterocystoplasty, a bladder augmentation using an intestinal segment. However, the use of bowel tissue is associated with numerous complica-tions such as metabolic disturbance, stone formation, urine leakage, chronic infections and malignancy. Urinary diversions using engineered bladder tissue would obviate the need for bowel for bladder reconstruction. Despite impressive progress in the field of bladder tissue engineering over the past decades, the successful transfer of this approach into clinical routine still represents a major challenge. We review major achievements and challenges in bladder tissue regeneration with a focus on different strategies to overcome the obstacles and to meet the need for living functional tissue replacements with a good growth potential and a long life span matching the pediatric popululation.